A Study for Improved Prediction of the Cutting Force and Chip Shrinkage Coefficient during the SKD11 Alloy Steel Milling - Thi-Bich Mac; The-Thanh Luyen; Duc-Toan Nguyen (Machines, 2022)
This study proposed an innovative method for improving the prediction of the cutting force (F) and chip shrinkage coefficient (K) for milling of SKD11 alloy steels using simulations and experimental results. Preliminary experimental measurements of the F and K were made for variable cutting speeds and depths, and simulations were then conducted using the Johnson–Cook model. However, significant discrepancies between the experiments and simulations were observed for the F and K. Therefore, an improved method was proposed, utilizing the relationship between simulation/experimental cutting forces and the equivalent fracture strain of simulation elements in the shear zone in the space of the stress triaxiality and equivalent strain. The progression of fracture strain paths according to the stress triaxiality until the desired cutting forces were achieved was utilized for adding new data to the fracture strain locus in the space of the stress triaxiality and equivalent strain. The new fracture strain locus was adopted again, to simulate and predict the F and K at full 2 × 3 levels of cutting speeds and cutting depths, and the results were compared with those of the corresponding experiments. Based on the highest deviations between the simulation and experimental data for the cutting force (5.29%) and chip shrinkage coefficient (5.08%), this study confirmed that the proposed method for determining the new fracture strain locus can improve the prediction of the F and K for milling of SKD11 alloy steels.